2021
DOI: 10.1002/mdc3.13363
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Features of Punding and Hobbyism in Parkinson's Disease

Abstract: Background Little is known about the cognitive and neuropsychiatric profile associated with punding and hobbyism in Parkinson's disease (PD). Objective To compare the clinical and neuropsychological features of PD patients with punding and hobbyism to PD controls. Methods The Questionnaire for Impulsive‐Compulsive Disorders in Parkinson's Disease‐Rating Scale (QUIP‐RS) was used as a screening tool, and a structured interview was used to diagnose punding/hobbyism. Clinical and neuropsychological assessment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Furthermore, the pathophysiology of punding and DDS differs from that of other ICBDs, with the pulsatility of L-dopa in advanced-stage disease being recognized as a key risk factor. 11,[25][26][27] It is important to mention that especially regarding DDS and punding, there is a lack of evidence-based studies which makes clinical decisions more dependent on clinical expertise. Most important in this context is the involvement of significant others 3 and supervised administration of medication alongside a multistep approach focusing first on stopping rescue doses of L-dopa and apomorphine, then reducing overall L-dopa dosage, and then applying second-line treatment strategies such as fractionation of L-dopa dosage, STN-DBS, CBT, clozapine, quetiapine, and antidepressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the pathophysiology of punding and DDS differs from that of other ICBDs, with the pulsatility of L-dopa in advanced-stage disease being recognized as a key risk factor. 11,[25][26][27] It is important to mention that especially regarding DDS and punding, there is a lack of evidence-based studies which makes clinical decisions more dependent on clinical expertise. Most important in this context is the involvement of significant others 3 and supervised administration of medication alongside a multistep approach focusing first on stopping rescue doses of L-dopa and apomorphine, then reducing overall L-dopa dosage, and then applying second-line treatment strategies such as fractionation of L-dopa dosage, STN-DBS, CBT, clozapine, quetiapine, and antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,[19][20][21][22][23][24] DDS and punding exhibit distinct clinical and pathophysiological characteristics when compared to the other ICBDs. 11,[25][26][27] Punding is defined as stereotyped behavior characterized by excessive nongoal-oriented, repetitive activities such as sorting things, tidying, taking objects apart, or collecting objects. 28,29 Individuals with punding typically consume higher-than-average doses of L-dopa, exhibit more dyskinesia, and are more prone to overuse dopaminergic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that depression was more frequent in patients with hobbyism/punding than in those without 20 . PD patients with punding showed higher levels of anxiety in a different study 22 …”
Section: Resultsmentioning
confidence: 90%
“…An association between punding and psychiatric comorbidities as well as cognitive impairments was indeed also found. A possible explanation for this association could be the underlying frontal lobe dysfunctions, 22 which has been supported by neuroimaging studies showing prefrontal cortical thinning in PD patients with punding 24,25 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation